"For me I see MINE to be a family sickness" – consumers understanding and perception of the etiology of mental illness in community-based residential facilities in Ghana. Issue 1 (2nd January 2022) - Naomi, Gyamfi; Kwadwo Wisdom, Mprah; Mensah, Isaac; Collins Kwabena, Boye; Anderson Mensah, Philip; Badu, Eric
ABSTRACT: This paper explores consumers' understanding and perception of the etiology of mental illness in community-based residential facilities in Ghana. Qualitative data involving in-depth interviews were used to collect data from 15 consumers of mental health services from two residential facilities. Thematic analysis was used to analyze the data. The study showed that mental illness is generally constructed within the medical and religious-cultural notion. The religious-cultural construction aligned mental illness to Ghanaian belief systems (supernatural forces, spirituality and traditional belief) and cultural practices (social norms and values) whilst the medical construction ascribed the etiology to biological, emotional and substance abuse issues. Although consumers had a positive perception of mental illness, they were doubtful about the presence of illness. The study concludes that the combination of medical, social and religious-cultural constructs and understanding of mental illness should be integrated into advocacy and awareness programmes to better educate consumers and clinicians.